Aphasia, alexia, and agraphia - Purdy, Mary (Reference Module in Neuroscience and Biobehavioral Psychology Encyclopedia of Mental Health (Second Edition), 2016)
Aphasia is a general language disorder resulting from brain damage, and alexia and agraphia are specific impairments in reading and writing, respectively. This article describes the symptoms associated with each disorder, the subtypes of each impairment, and the common causes. Assessment and management approaches consistent with the World Health Organization International Classification of Functioning (WHO-ICF) are briefly reviewed. © 2016 Elsevier Inc. All rights reserved.
Keywords: Acquired language disorders; Agraphia; Alexia; Aphasia; Assessment; Communication disorder; Dysgraphia; Dyslexia; Dysphasia; Management; WHO-ICF; dept.cmd